Examination of irradiated neuroblastoma and neuroepithelial cell lines for the interrelationship between cell survival, micronucleation, apoptosis and DNA repair - Akudugu, John Mbabuni (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.)--Stellenbosch University, 2000.